Developing Non-Structural Mitigation Strategies for Disaster Impact Reduction: A Case of Tidal Flood in Panimbang District, Indonesia - Syifa Hanifa; Djati Mardiatno; Dina Ruslanjari (Jagratara: Journal of Disaster Research, 2026)
Coastal areas are among the regions most vulnerable to climate change impacts, particularly sea-level rise and tidal inundation flooding. Panimbang District, located in Pandeglang Regency, Indonesia, is characterized by low-lying coastal plains and has experienced recurrent tidal flooding events, resulting in significant impacts on residential areas and public infrastructure. Given the increasing frequency and intensity of climate-related hazards, effective disaster risk reduction strategies are required to enhance community resilience. This study aims to analyze the hazard of tidal inundation flooding caused by sea-level rise, assess the vulnerability of residential and tourism areas, and formulate non-structural mitigation strategies to reduce flood risk. The research employs a qualitative assessment which non-structural mitigation measures are formulated through in-depth interviews with policymakers and community stakeholders. The interview results are analyzed using a qualitative SWOT framework. The findings indicate that the coastal community participation, supported by local organizations such as Tourism Awareness Groups (Pokdarwis) and Disaster Preparedness Cadets (Tagana), represents a significant opportunity for strengthening non-structural mitigation efforts. The study concludes that community-based participation, risk awareness enhancement, stakeholder collaboration, and locally tailored disaster management policies are essential components of effective tidal flood risk reduction. The resulting mitigation strategies provide practical guidance for disaster management planning and climate change adaptation in coastal areas.